PENGARUH LINGKUNGAN KERJA TERHADAP LOYALITAS KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA PT. ASELI DAGADU DJOKDJA. - Siti Rohimah (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
The purpose of this study is to know: (1) the influence of work environment affecting job satisfaction; (2) influence of job satisfaction affect to employee loyalty; (3) the influence of work environment affecting employee loyalty; (4) the influence of the work environment with the mediated job satisfaction on employee loyalty and also how much influence. This research is a quantitative research . Population in this research is employees of PT. Aseli Dagadu Djokdja. The sample of research is 63 respondents. Data collection was done by questioner method that was distributed to 63 respondents. Data analysis technique used is regression analysis supported by classical assumption test, F test, T test, and path analysis test, with the help of SPSS computer program version 17.0. Result of data analysis with significance 0,05 or 5% indicate that work environment have positive and significant effect to job satisfaction with t-count value bigger than t-table (6,171> 1,6706) with probability (0,000) smaller than significant level 0.05. Job satisfaction has positive and significant effect on employee loyalty with t-count value greater than t-table (16,948> 1,67076) with probability (0,000) smaller than significant level 0,05. The work environment has a positive and significant impact on employee loyalty with t-hit value greater than t-table (9,903> 1,6706) with probability (0,000) smaller than significant level 0,05. And work environment have positive and significant effect to employee loyalty with satisfaction as intervening variable at PT. Aseli Dagadu Djokdja. This can be seen in the results of path analysis which resulted in a total influence value greater than direct effect (1.377> 0.785).